Detection of genetically modified rice: Collaborative validation study of a PCR based detection of genetically modified rice Oryza sativa commercially available in Saudi Arabia - Alaraidh, Ibrahim; Amid, Azura; Abd-El Aziem, Farouk; Ibrahim, Mohamed M.; Bazaid, Salih; Greiner, Ralf; Alghunaim, Abdullah (Istanbul University Printing House, 2011)
A collaborative trial study has been conducted for validation of an extraction method and a subsequent PCR for the detection of transgenic rice sold in Saudi Arabia. The tests were carried out in Saudi Arabia using Real-Time PCR and the positive samples were validated in another lab in Malaysia using PCR and agarose gel visualization. The samples were tested for the existence of the NOS Terminator. A total of 150 samples were tested out of which three samples tested positive as GM-rice which were retested in Malaysia. The presence of GMO rice in Saudi Arabia supports the necessity of developing precise quantitative and qualitative ways for routine analyses and detection of GMO products in the Saudi Arabian market. With the discovery of GM products in the Saudi Arabian market it would be of no surprise that other Middle Eastern nations also knowingly or unknowingly import GM crops.